TAX BUOYANCY AND TAX ELASTICITY OF THE PROPORTIONAL INCOME TAX IN BULGARIA - Filipova, Milena; Tanchev, D. Stoyan (Revista Inclusiones, 2021)
This article studies the influence of economic growth on the collectability of proportional income tax revenues in Bulgaria. Using VAR models the relations between the tax buoyancy and tax elasticity of the proportional tax and the GDP are modelled for the period from March 2008 through March 2020. The conclusions drawn from the empirical analysis prove that the collectability of the revenue from proportional tax shows no increase. Changes in economic growth do not bring to changes in the revenue from proportional tax on income in Bulgaria.